Analysis of The Style of Learning Based on Visual, Auditorial, Kinesthetic on Students of Computer System - Ni Wayan Suardiati Putri; Ni Kadek Suryati (IJECA (International Journal of Education and Curriculum Application), 2020)
This study aims to describe the results of analysis of student learning styles based on Visual, Auditorial, Kinesthetic Computer System Study Program Class of 2019. The research method used is descriptive. Descriptive research was chosen because the researcher would describe and present a complete picture of the condition or relationship by describing each variable. The sample selection is done by purposive random sampling. The instruments used in this study were visual, auditory, and kinetic learning style questionnaires. Based on the research results it is known that the students of the Computer System Study Program in 2019 have a tendency towards kinesthetic learning styles. From 124 students, it was found that 13% Visual, 35% Auditorial, 42% Kinesthetic, 3% Combined Visual and Auditorial, 5% Combined Visual and Kinesthetic, and 2% Combined Auditorial and Kinesthetic.